(untitled) (Ameghiniana, 2013)
Abstract. A new tritheledontid, Irajatherium hernandezi gen. et sp. nov., from the Late Triassic Caturrita Formation of Brazil is described. The specimen consists of a left maxilla bearing the canine, five postcanines, and the alveolus of another one, two fragments of lower jaw, a humerus, and a femur. The association of the following features is unique for this taxon: 1) anterior upper postcanines transversely narrow bearing a higher cusp A and smaller cusp C; 2) last upper postcanines with higher, bulbous cusp A and smaller lingual cusps B and C, differing from Pachygenelus in lacking a buccal cingulum; 3) middle lower postcanines bearing a higher anterior cusp and three consecutively smaller posterior cusps, differing from Pachygenelus in lacking a lingual cingulum; 4) lower postcanines with sharp wear facets; 5) humerus with two thick osseous processes for the teres major muscle; and 6) femur with the greater trochanter at the head level and the lesser trochanter on the medial surface of the shaft. Our phylogenetic analysis placed I. hernandezi together with Riograndia guaibensis Bonaparte et al., Chaliminia musteloides Bonaparte, Pachygenelus monus Watson and Diarthrognathus broomi Crompton. These taxa represent the family Tritheledontidae. The presence of two kinds of upper postcanines in different replacement waves in Irajatherium could be a useful feature for inference of possible mechanism of dental differentiation among non-mammalian cynodonts. Possible fossorial adaptations are documented in the humerus of Irajatherium. Resumen. UN NUEVO TRITHELEDÓNTIDO (THERAPSIDA, EUCYNODONTIA) DEL TRIÁSICO TARDÍO DE RÍO GRANDE DO SUL, (BRASIL) Y SU POSICIÓN FILOGENÉNETICA ENTRE EUCINODONTES CARNÍVOROS NO MAMALIANOS. Se describe un nuevo tritheledóntido, Irajatherium hernandezi gen. et sp. nov., de la Formación Caturrita del Triásico Tardío de Brasil. El espécimen consiste en un maxillar izquierdo con el canino, cinco postcaninos y el alvéolo para uno más, dos fragmentos de mandíbula, un húmero y un fémur. La asociación de los siguientes caracteres es única para este taxón: 1) postcaninos superiores anteriores transversalmente angostos, con la cúspide A prominente y la cúspide C de pequeño tamaño; 2) último postcanino con la cúspide A prominente y bulbosa, y las cúspides B y C pequeñas desplazadas lingualmente, diferente a Pachygenelus por la ausencia de un cíngulo bucal; 3) dientes inferiores medios con una cúspide anterior alta y tres cúspides consecutivamente menores, diferentes de Pachygenelus por la ausencia de un cíngulo lingual; 4) facetas de desgaste en los postcaninos inferiores; 5) húmero con dos robustas tuberosidades para el músculo teres major; y 6) fémur con el trocánter mayor ubicado al nivel de la cabeza y trocánter menor proyectado medialmente. Nuestro análisis filogenético ubica a I. hernandezi junto con Riograndia guaibensis Bonaparte et al., Chaliminia musteloides Bonaparte, Pachygenelus monus Watson, and Diarthrognathus broomi Crompton. Estos taxones representan la familia Tritheledontidae. La presencia de dos tipos distintos de morfologías de postcaninos superiores involucrados en el recambio dentario de Irajatherium podría ser un rasgo importante para inferir sobre posibles mecanismos de diferenciación dentaria entre cinodontes. Se documentan posibles adaptaciones fosoriales en el húmero de Irajatherium.